2021
DOI: 10.1063/5.0049103
|View full text |Cite
|
Sign up to set email alerts
|

Strongly heat-assisted spin–orbit torque switching of a ferrimagnetic insulator

Abstract: Ferrimagnetic insulators promise low-power and high-speed spintronic applications, thanks to their insulating nature and fast dynamics near compensation points. In a ferrimagnetic insulator/heavy metal heterostructure, we investigate field- and current-induced magnetization switching at various temperatures and observe distinct magnetization switching behaviors owing to spin–orbit torque (SOT) and heating effect. We have realized SOT switching across the magnetization compensation temperature and discovered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Thermal effects in current‐induced spin‐orbit torque switching have been extensively studied in the literature and it was shown that it can lead to a reduced value of the in‐plane field necessary to initially break the system symmetry or induce a crossing of the compensation point in synthetic ferrimagnets. [ 34–36 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal effects in current‐induced spin‐orbit torque switching have been extensively studied in the literature and it was shown that it can lead to a reduced value of the in‐plane field necessary to initially break the system symmetry or induce a crossing of the compensation point in synthetic ferrimagnets. [ 34–36 ]…”
Section: Resultsmentioning
confidence: 99%
“…Thermal effects in currentinduced spin-orbit torque switching have been extensively studied in the literature and it was shown that it can lead to a reduced value of the in-plane field necessary to initially break the system symmetry or induce a crossing of the compensation point in synthetic ferrimagnets. [34][35][36] The emergence of an intermediate resistance state when sweeping the current was observed in the SOT switching experiments for certain CoGd structures. As seen in Figure 2c for Pt/Co 73 Gd 27 /W, an intermediate resistance plateau appeared in the current switching hysteresis loops at low in-plane magnetic field.…”
Section: Spin-orbit Torque Switchingmentioning
confidence: 89%
“…This creates hurdles in detecting the current-indued SOT switching for ferrimagnetic systems, particularly in the vicinity of T comp . For instance, the current-switching polarity was not reported to change across T comp in TbIG/W and always happens in the Fe-dominated scenario because the actual measured temperature is always above T comp owing to the excess Joule heating . Co-rich and Tb-rich samples host the same current-switching polarity in ferrimagnetic CoTb owing to the Joule heating effect .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the current-switching polarity was not reported to change across T comp in TbIG/W and always happens in the Fe-dominated scenario because the actual measured temperature is always above T comp owing to the excess Joule heating. 37 Co-rich and Tb-rich samples host the same current-switching polarity in ferrimagnetic CoTb owing to the Joule heating effect. 38 Essentially, the large spin transparency at the GdIG/Pt interface can reduce the required injected charge current and decrease the excess Joule heating to some extent.…”
Section: ↑↓mentioning
confidence: 96%
“…Due to the easy detectability and ultrafast magnetic dynamics, ferrimagnets have recently attracted tremendous attention. The ferrimagnet’s two sublattices hold independent magnetizations and gyromagnetic ratios which respond differently to temperature. Therefore, ferrimagnets can provide an alternative platform to implement thermal-assisted (TA) j sw reduction. Unfortunately, few works have realized sufficiently large temperature impact on j sw in ferrimagnetic (FIM) devices to date, mainly due to the robust bulk perpendicular magnetic anisotropy (PMA) in thick ferrimagnets. , …”
mentioning
confidence: 99%